2006
DOI: 10.1021/jp0614291
|View full text |Cite
|
Sign up to set email alerts
|

Products and Reaction Sequences in Tetrahydrofuran Exposed to Low-Energy Electrons

Abstract: Electron-stimulated reactions in solid films of tetrahydrofuran (THF), condensed on Kr spacers deposited on a Pt substrate, or directly onto the substrate, were induced and monitored simultaneously with use of high-resolution electron-energy-loss spectroscopy in the ranges of vibrational and electronic excitations. The spectra of the molecular films obtained after a certain time of exposure to electrons at incident energies of 14 and 15.5 eV were analyzed and different products were identified. Besides an alde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
(76 reference statements)
5
12
0
Order By: Relevance
“…Figure 6 shows a sample electron energy loss spectrum. It is similar to the thin-film spectrum of Lepage et al [4] and Jäggle et al [7] and the gas-phase spectrum of Milosavljević et al [14]. The individual vibrations are only partially resolved, but the consultation of the spectroscopic vibrational levels, the table of which has been given by Lepage et al [4], and of the results of routine density functional theory (DFT) normal mode calculations [32,33], reveals that various types of vibrations have their characteristic energy ranges and can be studied individually.…”
Section: Differential Elastic Cross Sectionsupporting
confidence: 84%
“…Figure 6 shows a sample electron energy loss spectrum. It is similar to the thin-film spectrum of Lepage et al [4] and Jäggle et al [7] and the gas-phase spectrum of Milosavljević et al [14]. The individual vibrations are only partially resolved, but the consultation of the spectroscopic vibrational levels, the table of which has been given by Lepage et al [4], and of the results of routine density functional theory (DFT) normal mode calculations [32,33], reveals that various types of vibrations have their characteristic energy ranges and can be studied individually.…”
Section: Differential Elastic Cross Sectionsupporting
confidence: 84%
“…The last study is of special interest here since it identified a number of core-excited resonances. Complementary to the gas phase, series of experiments with THF deposited on a surface was performed by Lepage et al [25], Antic et al [26,27], Breton et al [28], Jäggle et al [29], and Park et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, low-energy electron interactions with tetrahydrofuran (THF), the simplest model of the furanose ring that links the phosphate groups in the DNA backbone, have been studied intensively by both experimental and computational [21,[24][25][26][27][28] methods. These studies have provided valuable information about processes relevant to understanding electron transport and reactivity in biological media, including vibrational [4,8,11,15,18] and electronic excitation [3,8,11,20,22,23], dissociative attachment [5,6,10,14,19], electron trapping and reactivity in condensed THF [7,11,13], and the elastic [8,[15][16][17]20] and total scattering [9,12,21] cross sections. Although the reported measurements of the elastic electron cross section are generally consistent, there are some disagreements at higher energies; more importantly, data below 6 eV collision energy are scant, with the only reported measurements being those of Allan [15].…”
Section: Introductionmentioning
confidence: 99%